Uji Toksisitas Subkronik Ekstrak Kulit Batang Bakau (Rhizophora Apiculata) Terhadap Kerusakan Ginjal Tikus Putih Jantan (Rattus Norvegicus) Galur Sparague Dawley - Maulana, Rifadly Yusril; Mustofa, Syazili; Busman, Hendri; Kurniawaty, Evi (CV. Jasa Sukses Abadi, 2026)
Toxicity testing is a test to detect toxic effects of a substance in a biological system to obtain characteristic dose-response data from the test preparation. Rhizophora apiculata contains compounds such as alkaloids, flavonoids, triterpenoids, steroids, saponins, and tannins. Tannins are active compounds with potential antioxidant properties. This study is an experimental study using a Posttest Only Control Group Design and was conducted over 28 days on 30 rats divided into 5 groups: the control group (K), Treatment Group 1 at 114 mg/kg body weight (P1), Treatment Group 2 at 228 mg/kg body weight (P2), Treatment Group 3 at 456 mg/kg body weight (P3), and Treatment Group 4 at 912 mg/kg body weight (P4). Data were analyzed using the Kruskal-Wallis statistical test and the Mann-Whitney Post Hoc test. Based on the results of the Kruskal-Wallis statistical test, a p-value of 0.000 was obtained. Meanwhile, based on the results of the Mann-Whitney Post hoc statistical test, groups K, P1, P2, P3, and P4 showed significant differences (p<0.05), while groups P2 and P3, which received intervention or treatment, showed insignificant differences. Administration of mangrove bark extract (Rhizophora apiculata) for 28 days had a toxic effect on the kidneys at a dose of 114 mg/kgBW, with toxic effects in the form of tubular edema and glomerular edema. At doses of 228 mg/kgBW, 456 mg/kgBW, and 912 mg/kgBW, Higher doses resulted in more severe toxic effects on the histopathology of the kidneys of Sprague Dawley rats, as evidenced by tubular edema, glomerular edema, Bowman's space edema, and inflammatory cells.